2019
DOI: 10.3389/fncel.2019.00282
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes and Neurovascular Function in the Healthy and Diseased Brain

Abstract: Pericytes are multi-functional cells embedded within the walls of capillaries throughout the body, including the brain. Pericytes were first identified in the 1870s, but little attention was paid to them during the following century. More recently, numerous vascular functions of pericytes have been identified including regulation of cerebral blood flow, maintenance of the blood-brain barrier (BBB), and control of vascular development and angiogenesis. Pericytes can also facilitate neuroinflammatory processes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
232
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(236 citation statements)
references
References 63 publications
2
232
0
2
Order By: Relevance
“…The neurovascular unit (NVU) is a complex structure organized by endothelial cells, intimately associated with pericytes and astrocytic endfeet to form the BBB. Parenchymal cells including excitatory neurons, regulatory interneurons and microglia actively interact with the NVU [121]. As central components of the NVU, pericytes represent the first line of immunological defense as antigen-presenting cells, playing a pivotal role in the maintenance of the BBB and microvascular stability.…”
Section: The Implication Of Ad Immune-risk Factors and Glial Responsementioning
confidence: 99%
“…The neurovascular unit (NVU) is a complex structure organized by endothelial cells, intimately associated with pericytes and astrocytic endfeet to form the BBB. Parenchymal cells including excitatory neurons, regulatory interneurons and microglia actively interact with the NVU [121]. As central components of the NVU, pericytes represent the first line of immunological defense as antigen-presenting cells, playing a pivotal role in the maintenance of the BBB and microvascular stability.…”
Section: The Implication Of Ad Immune-risk Factors and Glial Responsementioning
confidence: 99%
“…These cells were originally described in late 19th century (Eberth, 1871;Rouget, 1873) and initially named "pericytes" in 1923 by Zimmermann (Zimmermann, 1923) in accordance with their location enveloping the endothelium, and their being embedded in the basement membrane outside the microvessels (Zimmermann, 1923;Armulik et al, 2011;Geranmayeh et al, 2019). Although pericytes were considered to contribute to architectural maintenance and contraction of capillaries (Sandison, 1931;Zweifach, 1934;Clark and Clart, 1940), little had been known about their multifunctional characteristics and roles in neurological disorders until late 20th century (Brown et al, 2019). In the last 20 years, however, using a combination of markers and advancing technologies, a variety of functions of pericytes in health and disease have been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the pericyte at the NVU has become evident in recent years [32]. For example, Nikolakopoulou et al [33] have now shown that pericyte ablation results in vascular dysfunction, including BBB breakdown and reduced blood flow, and neuronal loss.…”
Section: Crosstalk and Cellular Signaling Within The Nvumentioning
confidence: 99%